THE PREPARATION OF POLISH SOCIAL WORKERS TO WORK WITH PERSON EXPERIENCING DOMESTIC VIOLENCE. EDUCATIONAL EXPERIENCES AND CHALLENGES - Łukasik, Joanna Małgorzata; Pikuła, Norbert Gerard; Jagielska, Katarzyna Agata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Today’s social worker has to face many new challenges that arise due to socio-economic and cultural changes. One of the extremely important and difficult areas of social workers' job is to work with people who are experiencing domestic violence. The aim of the following article is to show previous experience in the field of theoretical and practical social worker's training in work with people experiencing domestic violence and the difficulties arising because of the imperfections of the system (i.e. due to lack of appropriate diagnostic tools, intervention strategies and supporting institutions). To show the weaknesses of education, a secondary analysis of the data (including programs, study plans) was made and expert interviews with employees who undertake work with a person experiencing violence were conducted. The analysis allowed to propose a concept of social workers’ training in working with a person experiencing domestic violence (child, woman, elderly person), based on best practices, i.e. from Israel and Canada.